Przeżywalność i wzrost pędraków Melolontha spp. na korzeniach głównych gatunków drzew leśnych - Woreta, Danuta; Sukovata, Lidia (Leśne Prace Badawcze, 2014)
The survival, weight and relative growth rate (RGR) of the Melolontha spp. grubs feeding on roots of Quercus petraea , Q. robur , Fagus sylvatica , Betula pendula , Larix decidua , Alnus glutinosa and Pinus sylvestris were examined. Overall, the youngest grubs, L1, were the most affected by food quality. The mortality of the grubs feeding on the roots of A. glutinosa changed most rapidly and, consequently, LT50 was the shortest (25.9 days), whereas the slowest changes in mortality with the highest LT50 values were observed on the two oak species (54.9 and 44.9 days on Q. robur and Q. petraea , respectively). The RGRs of the L1 grubs were the highest on oaks, F. sylvatica and B. pendula . The overall rate of survival of the older grubs was high (66.7-100%). It was the lowest on the roots of B. pendula (L2 grubs) and L. decidua (L3 grubs), which at the same time displayed the highest RGRs. The interpretation of the results is difficult due to the lack of basic knowledge on the potential effects of food quality and other factors on grub metamorphosis. There is no doubt, however, that among the seven tested tree species the roots of A. glutinosa are the least favorable for the Melolontha grubs’ performance.